2016
DOI: 10.1186/s13054-016-1419-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine and esmolol on systemic hemodynamics and exogenous lactate clearance in early experimental septic shock

Abstract: BackgroundPersistent hyperlactatemia during septic shock is multifactorial. Hypoperfusion-related anaerobic production and adrenergic-driven aerobic generation together with impaired lactate clearance have been implicated. An excessive adrenergic response could contribute to persistent hyperlactatemia and adrenergic modulation might be beneficial. We assessed the effects of dexmedetomidine and esmolol on hemodynamics, lactate generation, and exogenous lactate clearance during endotoxin-induced septic shock.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 55 publications
0
29
1
2
Order By: Relevance
“…; Hernández et al. ), our results revealed that esmolol had a negative effect on the macrocirculation and failed to improve the affected microcirculation. These negative effects could be explained by a decrease in RV function.…”
Section: Discussioncontrasting
confidence: 43%
“…; Hernández et al. ), our results revealed that esmolol had a negative effect on the macrocirculation and failed to improve the affected microcirculation. These negative effects could be explained by a decrease in RV function.…”
Section: Discussioncontrasting
confidence: 43%
“…As alpha-2 agonist, dexmedetomidine may increase the risk of hypotension and bradycardia [ 14 , 15 ] and, in patients with septic shock, this may be both dangerous and harmful. However, experimental data also suggest that dexmedetomidine can be administered in septic shock and may even have catecholamine-sparing effects [ 5 , 16 21 ]. Our findings are consistent with such experimental observations.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that DEX increased the pressor response to norepinephrine without adverse consequences on tissue perfusion in rats with sepsis. (27,28) Although the alfa-2 adrenergic receptor is a known mechanism of controlling blood pressure by negative feedback on sympathetic neuronal fibers, this inhibitory effect of dexmedetomidine has a small effect on blood pressure (11,29). In addition, inflammatory cytokines such as TNF-α, IL-β, and NO can inhibit the systolic function of the heart and dilating peripheral blood vessels (30 32), and these inflammatory cytokines can damage the capillary endothelial cells, causing capillary leakage, thereby reducing the effective circulation capacity (33).…”
Section: Discussionmentioning
confidence: 99%